Utilization of Telemedicine for Medical Staff As a Impact of the Industrial Revolution 4.0 - Nurhayati; Muh Afif Ali Imron (LPPM Universitas Duta Bangsa Surakarta, 2019)
Industrial Revolution 4.0 is influential in changing patterns of human work characterized by the emergence of remote medicine (telemedicine), biotechnology, data automation and artificial intelligence. The health service sector benefited from the industrial revolution 4.0. It is important for medical staff to know technological developments in the health sector so that the welfare of the community can increase and not lose competitiveness with other parties. Health care providers explore the potential of telemedicine for remote monitoring and treatment of patients through devices connected to the internet. The aim of this study describes the use of telemedicine for medical staffs as a result of the emergence of the industrial revolution 4.0. The method used in this study is a qualitative method by means of literature review that focuses on the use of telemedicine. Result of this study The application of telemedicine has an impact on improving patient health and the skills of medical staffs in conducting care. Gaps in the distribution of internet networks are challenges that the government has in developing telemedicine. The government should carry out cross-sectoral collaboration in the development of telemedicine